A recommended practical approach to the management of target therapy and angiogenesis inhibitors cardiotoxicity: an opinion paper of the working group on drug cardiotoxicity and cardioprotection, Italian Society of Cardiology. (May 2016) - Maurea, Nicola; Spallarossa, Paolo; Cadeddu, Christian; Madonna, Rosalinda; Mele, Donato; Monte, Ines; Novo, Giuseppina; Pagliaro, Pasquale; Pepe, Alessia; Tocchetti, Carlo G.; Zito, Concetta; Mercuro, Giuseppe
Abstract : The US National Cancer Institute estimates that cardiotoxicity (CTX) from target therapy refers mostly to four groups of drugs: epidermal growth factor receptor 2 inhibitors, angiogenic inhibitors, directed Abelson murine leukemia viral oncogene homolog inhibitors, and proteasome inhibitors. The main cardiotoxic side-effects related to antiepidermal growth factor receptor 2 therapy are left ventricular systolic dysfunction and heart failure. Angiogenesis inhibitors are associated with hypertension, left ventricular dysfunction/heart failure, myocardial ischemia, QT prolongation, and thrombosis. Moreover, other agents may be related to CTX induced by treatment. In this study, we review the guidelines for a practical approach for the management of CTX in patients under anticancer target therapy.